Degenerate Representation and Racism in Heart of Darkness - Paudel, Yog Raj (Janapriya Journal of Interdisciplinary Studies, 2022)
This paper has analyzed Joseph Conrad’s Heart of Darkness from Orientalist perspective. The term “Orientalism” has been a critical tool after Edward Said described how understanding of Europe about the non-Europeans became a weapon of maintaining power over the latter. This research has applied analytical and interpretivist approaches in discussion. The objective is to pinpoint why and how colonial rulers in the novel stereotypically produce representations of the Orient (here African is included) and create a false illusion that the West is “self” and the East is “other”. The selected text is analyzed in light of Edward Said’ description of the stereotypes of Oriental land and race as strange, inferior and wild. The search shows that Conrad presents Africans as uncivilized people, living in backward condition. He derogatorily describes them in their physical appearance and social behavior. Congo land is presented as wild, uncommon and mysterious. Europeans in the novel express their obsession that they are intelligent, skilled and much superior to the native and try to justify the colonial rule as an effort to civilize the African race and develop the place.